The world's rarest birds - Hirschfeld, Erik; Swash, Andy; Still, Rob (WildGuides., 2013)
This illustrated book vividly depicts the most endangered birds in the world and provides the latest information on the threats each species faces and the measures being taken to save them. Today, 571 bird species are classified as critically endangered or endangered, and a further four now exist only in captivity. This landmark book features stunning photographs of 500 of these species--the results of a prestigious international photographic competition organized specifically for this book. It also showcases paintings by acclaimed wildlife artist Tomasz Cofta of the 75 species for which no photographs are known to exist.